Метод разрешающих функций для решения задачи преследования при интегральных ограничениях на управления - Саматов, Б.Т. (Проблемы управления и информатики, 2013)
Досліджено задачу переслідування в лінійних диференціальних іграх з інтегральними обмеженнями за допомогою методу розв’язувальних функцій Чикрія. Запропоновано побудову розв’язувальної функції, що обґрунтовує правило паралельного зближення гравців, тобто -стратегію для переслідувача. Для даного випадку отримано нові достатні умови Понтрягіна до розв’язності задачі переслідування. Як приклад наведено два класи ігор, кожен з яких може становити певний інтерес. The pursuit problem for linear differential games with integral constraints on the player’s controls is considered. The problem solving is based on the Chikriy resolving functions method. It is proposed the construction of resolving function substantiating the rule of players’ parallel-approach, namely — -strategy for pursuer. For the considered case the new Pontryagin sufficient conditions are obtained for the solvability of the pursuit problem. As an example two classes of games are adduced: namely the Pontryagin’s control example and the simple pursuit problem for the case «l-catch» of evader.